Chemical bonding successful learning using the "Chebo collect game": A case study - Achmad Lutfi; Rusly Hidayah; Sukarmin Sukarmin; Kusumawati Dwiningsih (OmniaScience, 2021)
The use of games in the chemistry learning process has a positive effect on students' behavior, understanding, and interest in the discussed topics. A Chebo Collect (chemical bonding collects) game, which has met validity, practicality, and effectiveness criteria, is used as a medium to learn chemical bonds. This study aims to assess the use of computerized games as learning media on chemistry subjects based on the learning activities, students' responses, and the impact of learning objectives achievement. This study was conducted on high schools in East Java, Indonesia with 32 students as the subject for a game teaching method and 30 students as control using a traditional method. The students' activities were observed during the learning process and the tests were done using a questionnaire. The results revealed that the learning activities were more student-centered method's and the learning outcomes reached classical completeness with the significant differences between the initial and final test scores. Students also gave positive responses to the use of Chebo collect game as a medium to learn chemical bonds. Chebo Collect game has succeeded in helping students to learn chemical bonds by making the learning a student-centered one and improving students' learning outcomes.